The coupling of South American soybean and cattle production frontiers: new challenges for conservation policy and land change science - Gasparri, Nestor Ignacio (2014)
Different drivers and places of land use change in South America have often been studied in isolation. Evidence suggests, however, that in many instances, both places and drivers are becoming increasingly interconnected. The growing diversification and internationalization of agricultural commodity chains is creating new linkages across production frontiers and sectors that have important implications for conservation. In this article, we explore the implications of the sectoral and geographical coupling of soybean and cattle production frontiers for forest conservation in South America, with particular attention to the potential for policy-induced deforestation leakage. We conclude that the existence of coupled frontiers creates a need for more actor-centered approaches to conservation policy and research.